MOTIVASI PEMANENAN KAYU RAKYAT BERDASARKAN KARAKTERISTIK PETANI HUTAN RAKYAT (Studi Kasus: di Desa Lumban Silintong, Kecamatan Pagaran, Kabupaten Tapanuli Utara, Sumatera Utara) - Simamora, Roza D.; M. Mardhiansyah, M. Mardhiansyah; Darlis, Viny Volcherina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Harvesting of community timber is part of community forest management.Harvesting behavior is caused by harvesting motivation arising from the urgent need of life. Farmers will harvest crops if they are considered to be profitable even though they are not yet ripe, such as the cost of education, health costs, and other needs that exist in farm households in Lumban Silintong Village.The aim of this research was toidentify the characteristics of smallholder forest farmers in Lumban Silintong Village and to find out the motivation of harvesting of community timber in Lumban Silintong Village. Sampling method using porposive sampling.Data processing method used is descriptive method. Based on the result of the research, it can be seen that the characteristics of smallholder forest farmers in Lumban Silintong Village who have used the dominant wood harvesting in the age group of 15-64 years as many as 31 people (77.50%) belong to the productive age, Senior High School as many as 23 people (57.50%), with experience trying to farm for 31-40 years as many as 11 people (27.50%). Smallholder forest farmers in Lumban Silintong Village are harvesting timber with various motivations, the most dominant people harvesting motivation is education cost motivation.Â Keywords: Harvesting of community timber, harvesting motivation, farmer characteristics.Â